Assessing of adaptation ability of Listeria to benzalkonium chloride (BAC) by determination of its minimal inhibitory concentration - Monika PODPAC; Barbara JERŠEK (Acta Agriculturae Slovenica)
Bacteria of the genus Listeria pose a problem in the food industry due to their wide distribution and their good survival in adverse conditions. L. monocytogenes (E. Murray et al. 1926) Pirie 1940 is human pathogen, while L. innocua Seeliger (ATCC® 33090™) as not pathogenic bacteria is the most often found listeria in food production environment. Disinfectants represents an important part of Listeria management in food processing environments and benzalkonium chloride (BAC) is used frequently. The purpose of the work was to determine whether strains of listeria can adapt to BAC. To carry out the adaptation, a precise determination of antibacterial activity of BAC was needed. Firstly minimum inhibitory concentration (MICMTP) of BAC was determined with broth microdilution method for each Listeria strain. Then, we checked whether MICMTP was indeed the lowest concentration of BAC, which had an influence on growth of strains with growth curves. We found out that growth inhibitory effect (MICGC) was achieved at concentrations of BAC that were lower than MICMTP (0.1-0.5x of MICMTP values). Adaptation of listeria to BAC was therefore performed by using 0.25x MICGC as the initial BAC concentration. Results showed that 50 % of the strains were able to adapt to BAC, and in L. monocytogenes ŽM500 this adaptation was even stable. The broth microdilution method was useful for approximate assessment of antimicrobial activity of BAC, while for the more precise determination of disinfectant activity it is necessary to determine it by using another method such as plate count method.